Photosynthetic Pigments with Potential for a Photosynthetic Antenna: A DFT Analysis - Jesús Francisco Monzón-Bensojo; Manuel A. Flores-Hidalgo; Diana Barraza-Jiménez (International Journal of Photoenergy)
Geometrical and electronic properties of the main photosynthetic pigments in higher plants such as chlorophylls and xanthophylls were studied to find potential candidates that were able to participate in an eventual zeolite-dye artificial antenna. CRDFT (chemical reactivity density functional theory) and TD-DFT (time-dependent DFT) methods were employed in ground-state and excited-state calculations, respectively. The evaluated electronic properties at the gas phase included (a) energies such as HOMO-LUMO band gap (H-L, ranging from 2.168 to 2.504 eV), adiabatic ionization potential (I, ranging from 5.964 to 7.207 eV), and adiabatic electronic affinity (A, ranging from 2.176 to 2.741 eV); (b) global chemical reactivity indexes such as electronegativity (χ, ranging from 4.121 to 4.974 eV), hardness (η, ranging from 1.812 to 2.233 eV), electrophilicity index (ω, ranging from 4.365 to 5.541 eV), and electroaccepting-electrodonating powers (ω+, ranging from 1.671 to 2.115 eV, and ω−, ranging from 4.375 to 5.273 eV); (c) electron-hole reorganization energies (λ, ranging from 0.225 to 0.519 eV and ranging from 0.168 to 0.425 eV, respectively) and electron-hole extraction potentials (EEP, ranging from 2.570 to 2.966 eV, and HEP, ranging from 5.538 to 7.012 eV, respectively); and (d) local chemical reactivity indexes like condensed Fukui functions (fk), condensed dual descriptor (f2r), and condensed local softness (sk). These electronic properties allowed the association between molecules and reactivity-selectivity criteria, under the context of charge transfer and electronic transitions. Also, the aforementioned electronic properties were determined for combinations made with the selected molecules (β-cryptoxanthin and zeaxanthin) and 5 solvents (n-hexane, diethyl ether, acetone, ethanol, and methanol) with upward dielectric constants (ε). From frequency calculations, IR spectra were obtained for combinations. Finally, excited-state computations were carried out to acquire UV-Vis spectra of the combinations. We conclude that the selection of dyes is controlled mainly by geometrical constraints rather than by electronic properties.